Homer, Troy and the Turks Heritage and Identity in the Late Ottoman Empire, 1870-1915 - Uslu, Günay (Heritage and Memory Studies, 2017)
Homer's stories of Troy are part of the foundations of Western culture. What's less well known is that they also inspired Ottoman-Turkish cultural traditions. Yet even with all the historical and archaeological research into Homer and Troy, most scholars today rely heavily on Western sources, giving Ottoman work in the field short shrift. This book helps right that balance, exploring Ottoman-Turkish involvement and interest in the subject between 1870, when Heinrich Schliemann began his excavations in search of Troy on Ottoman soil, and the battle of Gallipoli in 1915, which gave the Turks their own version of the heroic epic of Troy.